ER-mediated stress induces mitochondrial-dependent caspases activation in NT2 neuron-like cells - Arduíno, Daniela M. (2009)
Recent studies have revealed that endoplasmic reticulum (ER) disturbance is involved in the pathophysiology of neurodegenerative disorders, contributing to the activation of the ER stress-mediated apoptotic pathway. Therefore, we investigated here the molecular mechanisms underlying the ER-mitochondria axis, focusing on calcium as a potential mediator of cell death signals. Using NT2 cells treated with brefeldin A or tunicamycin, we observed that ER stress induces changes in the mitochondrial function, impairing mitochondrial membrane potential and distressing mitochondrial respiratory chain complex Moreover, stress stimuli at ER level evoked calcium fluxes between ER and mitochondria. Under these conditions, ER stress activated the unfolded protein response by an overexpression of GRP78, and also caspase-4 and-2, both involved upstream of caspase-9. Our findings show that ER and mitochondria interconnection plays a prominent role in the induction of neuronal cell death under particular stress circumstances. [BMB reports 2009; 42(11): 719-724]